Seasonal and Off-seasonal Vegetables Production in Maulvibazar District: Insight from Profitability, Price Variations and Risk Management Perspective - Maruf, Sadek Ahmed; Ahmed, Jasim Uddin; Khan, Jahangir Alam (Journal of the Bangladesh Agricultural University, 2024)
The research work was conducted to assess the comparative profitability, seasonal price variations and risk management strategies in seasonal and off-seasonal vegetables production by means of tomato and bean vegetables in Maulvibazar district. Both primary and secondary data were used. The study utilized tabular, mathematical and statistical techniques for data analysis. The study found that the BCR for the seasonal and the off-seasonal tomato production were 1.59 and 2.23, respectively, whereas the BCR for the seasonal and the off-seasonal bean production were 1.32 and 2.19, respectively. The study also found that, in season (November-March), the highest seasonal price index for both tomato and bean vegetables were found in November (i.e. 149.71 and 109.24, respectively). While in off-season (April-October), the highest seasonal price index for the tomato (i.e. 177.93) and the bean (i.e. 197.80) were found in September and August, respectively. In evaluating the risk management strategies, the study found that the frequency and the relative frequency of the application of manure and the use of insecticides were 100% for both season tomato and bean vegetables. On the basis of the findings and opinions of farmers during field visit, the researchers’ identified high cost of human labor, price fluctuation and deficiency of farmers’ awareness in term of different risk management strategies were the major problem. The researchers’ recommends that farmers should use friends’ contributory labor, planning appropriate harvesting period (i.e. early period for season and late period of off-season) and increasing farmers’ awareness by means of local and national level training. These findings will be helpful for farmers, researchers and policy makers to take informed production decision, formulation of future research work and policy development focusing vegetable sector of Bangladesh. J Bangladesh Agril Univ 19(1): 99–108, 2021 https://doi.org/10.5455/JBAU.48118